A multiple‐loop feedback control strategy suitable for different operation modes of microgrid. (15th February 2014) - Ma, Jing; Ding, Xiuxiang; Mi, Chao; Wang, Zengping; Yang, Qixun
Summary In order to achieve stable operation of the microgrid under different modes, a multiple‐loop feedback controller is designed in this paper using the inverter output voltage, the capacitor voltage, and the capacitor current as the feedback variable for the outer, middle, and inner loop, respectively. Control parameters are calculated by the combined method of Routh–Hurwitz criterion and pole assignment principle. The resulting external characteristic of distributed generation is that the output impedance is inductive in low frequencies and resistive in high frequencies, thus droop control among multiple inverter units in a microgrid can be achieved by means of wireless communication. The designed multiple controller can improve system stability and guarantee high quality output as well as fast dynamic response when microgrid operates in grid‐connected mode. It is capable of keeping load voltage and frequency stable and facilitating power sharing among different inverter units when the microgrid operates in islanded mode. Furthermore, smooth switching between different control strategies for different operating modes is convenient with the designed controller. With a simple design, the multiple‐loop controller is practical and easy to implement. Simulation results verify the reasonableness and effectiveness of this design. Copyright © 2014 John Wiley & Sons, Ltd.